Combining waterfowl and breeding bird survey data to estimate wood duck breeding population size in the Atlantic Flyway. Issue 7 (13th August 2015) - Zimmerman, Guthrie S.; Sauer, John R.; Fleming, Kathy; Link, William A.; Garrettson, Pamela R.
ABSTRACT We combined data from the Atlantic Flyway Breeding Waterfowl Survey (AFBWS) and the North American Breeding Bird Survey (BBS) to estimate the number of wood ducks (Aix sponsa) in the United States portion of the Atlantic Flyway from 1993 to 2013. The AFBWS is a plot‐based survey that covers most of the northern and central portions of the Flyway; when analyzed with adjustments for survey time of day effects, these data can be used to estimate population size. The BBS provides an index of wood duck abundance along roadside routes. Although factors influencing change in BBS counts over time can be controlled in BBS analysis, BBS indices alone cannot be used to derive population size estimates. We used AFBWS data to scale BBS indices for Bird Conservation Regions (BCR), basing the scaling factors on the ratio of estimated AFBWS population sizes to regional BBS indices for portions of BCRs that were common to both surveys. We summed scaled BBS results for portions of the Flyway not covered by the AFBWS with AFBWS population estimates to estimate a mean yearly total of 1, 295, 875 (mean 95% CI: 1, 013, 940–1, 727, 922) wood ducks. Scaling factors varied among BCRs from 16.7 to 148.0; the mean scaling factor was 68.9 (mean 95% CI: 53.5–90.9). Flyway‐wide, population estimates from the combined analysis were consistent with alternative estimates derived from harvest data, and also provide population estimates within states and BCRs. We recommend their use in harvest and habitat management within the Atlantic Flyway. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.